Stratigraphic-Tectonic Evolution and Characterization of the Carboniferous in the Karamay–Baikouquan Fault Zone in the Northwestern Margin of the Junggar Basin, Northwest China - Ma, Yinshan; Wang, Tao; Yang, Yazhou; Liu, Zhiwei; Zhang, Lei; Bai, Yu (Frontiers in Earth Science, 2022)
The northwestern margin of the Junggar Basin has a complex tectonic history, which is challenging for hydrocarbon exploration. This study highlights the structural patterns, tectonic evolution, and controlling factors of the Karamay–Baikouquan Fault Zone (KBFZ) in the northwestern margin of the Junggar Basin based on well-log and 3D seismic data. The main findings of this study include the following: spatially, we have divided the structural patterns of KBFZ into three zones on the plane, namely, northern, central, and southern zones; temporarily, the tectonic evolution has been divided into five stages from Late Carboniferous to Cretaceous, namely, Early-Middle Carboniferous, Late Carboniferous-Early Permian, Middle-Late Permian, Triassic-Middle Jurassic, and Late Jurassic-Cretaceous. During the Hercynian and Indochina orogeny, the compressional stress from the movement of the Dalabute strike-slip fault and the Genghis–Junggar strike-slip fault produced various degrees of deformation in different locations in the KBFZ. The general structural style is a mixture of strike-slip and thrust-nappe. The main controlling factors include stress period, stress direction, and stratigraphic-lithologic associations. This study has implications for hydrocarbon exploration and development in the northwestern margin of the Junggar Basin.